Molecular screening for Rickettsia, Anaplasmataceae and Coxiella burnetii in Rhipicephalus sanguineus ticks from Malaysia - Watanabe, Malaika; Nakao, R.; Babjee, Shaik Mohamed Amin; Moktar, Maizatul Akmal; Youn, J. H.; Qiu, Y.; Sugimoto, C. (Malaysian Society of Parasitology and Tropical Medicine, 2015)
A total of 44 Rhipicephalus sanguineus ticks collected from 23 dogs from Malaysia were screened for Rickettsia, Anaplasmataceae and Coxiella burnetii. Coxiella burnetii was detected in 59% (26/44) of ticks however Rickettsia and Anaplasmataceae were not detected in any of the ticks. In order to genotype the strains of C. burnetii, multispacer sequence typing (MST) was carried out using three different spacers. One of the spacers; Cox2 successfully amplified a fragment for which the full length sequence of 397 bp was obtained. The sequenced product revealed only a single nucleotide difference with the Cox2.3 type sequence.